Respuesta :

We can solve using BEDMAS.
We also must work from left to right.

-9 + (-11) - 4 + (-8) - 10=
-9 - 11 - 4 + (-8) - 10=
-20 - 4 + (-8) - 10=
-24 + (-8) - 10=
-24 - 8 - 10=
-32 - 10
= -42

The answer would be -42

Hope this helps!
-Benjamin

we can just rewrite them as sums of negatives
no need for order of operations
just add, a negative is just addition of a negative
a negative is just moving in oposite direction as positive

so
-9-11-4-8-10=
-20-4-8-10=
-24-8-10=
-32-10=
-42

answer is -42